IbM KELOMPOK TANI AGRO MADINA KELURAHAN KEJAWAN PUTIH TAMBAK, KECAMATAN MULYOREJO SURABAYA - Erma Yuliaty; Siti Mundari; Zainal Arief (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2015)
The village of Kejawan Putih Tambak, district of Mulyorejo, Surabaya is a coastal area. The majority of residentsâ€™sÂ condition in the village below the standard of living. Finally, a woman named Sita Pramesthi, planted markisa fruit and then processing into refined products that are markisa fruit juice, jam, porridge, and syrup. Among other, markisa syrup which is routinely produced because the market is better than others. This is why many people also planted markisa fruit in their yards. Currently in the villageof Kejawan Putih Tambak there have been five neighborhood association grow markisa fruit with a total of about 70 households. Therefore, in the urban village on February 2009 established theÂ markisa fruit farmers association named â€œKelompok Tani Agro Madinaâ€. But unfortunately the expectation to impoveÂ walfare ofÂ the society aroundÂ can not be expected because the syrup product is stale faster. For that reason, the IbMÂ team of Untag Surabaya proposes to conduct training on the manufacture and procurement of markisa syrup that are syrup mixing machine, instrument sterilizer product already packaged, and the toolsÂ to cover a bottle of syrup. After getting a good trainingÂ and a set ofÂ machine to make a good syrup product, there is a positive effect thatÂ demand is increasing. Success of this effort, the income residentâ€™s ofÂ Kejawan Putih Tambak is increasing.Through markisa syrup â€œKelompok Tani Agro Madinaâ€ received an award from The Mayor ofÂ Surabaya that is Mrs Tri Risma Harini in commemoration of Surabaya City to 721 in 2014 and the area of Kejawan Putih Tambak confirmed as â€œ Kampung Markisaâ€.Keywords : markisa fruit, markisa fruit syrup.